Current Practices of the Child Neurologist in Managing Sports Concussion. (January 2014) - Broshek, Donna K.; Samples, Hillary; Beard, Jennifer; Goodkin, Howard P.
Given the 2010 position statement issued by the American Academy of Neurology that neurologists be consulted on return-to-play decisions following a concussion, we surveyed members of the Child Neurology Society to asses clinical practice management of concussion among child neurologists. Among the 239 respondents, the majority continued to rely on the American Academy of Neurology's 1997 Practice Parameter to guide their decision-making process. Although the 2008 consensus statement from the Third International Conference on Concussion in Sport (Zurich Guidelines) is currently considered the most up-to-date guideline, few respondents relied exclusively on this guideline. More respondents who completed continuing medical education on concussion reported making clinical decisions based on the Zurich guidelines. The finding that child neurologists who completed continuing medical education had a greater familiarity with the more recently proposed consensus-based concussion guidelines supports the development of additional education in sports concussion at all levels of child neurology training.